2004
DOI: 10.1160/th03-05-0277
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen C-terminal peptidic sequences (Haptides) modulate fibrin polymerization

Abstract: We previously described synthetic peptides of 19-21 amino acid residues, homologous to the C-termini of fibrinogen Fib(340) and Fib(420), from the beta-chain (Cbeta), the extended alphaE chain (CalphaE) and near the end of the gamma-chain (preCgamma) which elicited attachment (haptotactic) responses from mesenchymal cells. We named these haptotactic peptides -Haptides. The effects of Haptides on fibrin clot formation was evaluated and their possible effects on platelet aggregation was examined. The Haptides Cb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In free form, Haptides tended to form multimers and nanoaggregates and significantly modulated the kinetics of fibrin coagulation reactions, resulting in decreased clotting time. [43][44][45] It is possible that the aggregation of heat denatured fibrinogen monomers into globular, multimeric structures (as shown in Figure 3) might be due in part to the binding interactions between heat-exposed Haptide epitopes of partially denatured fibrinogen monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In free form, Haptides tended to form multimers and nanoaggregates and significantly modulated the kinetics of fibrin coagulation reactions, resulting in decreased clotting time. [43][44][45] It is possible that the aggregation of heat denatured fibrinogen monomers into globular, multimeric structures (as shown in Figure 3) might be due in part to the binding interactions between heat-exposed Haptide epitopes of partially denatured fibrinogen monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining ( Figure 5) revealed that the heat denatured fibrin presented more exposed Haptide epitopes. In the light of the Haptotactic potency of these epitopes, 45,46 they probably contributed to the high cell binding potency of FMB, though other cell attachment sequences on fibrinogen might also be available. 52,53 However, when heated to 958C, the cell attachment potency of FMB were significantly reduced (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…These peptides were termed ‘Haptides’ because of their haptotactic (cell-binding) properties [12,13]. Haptides were initially studied as cell-binding domains on fibrin(ogen), which are not necessarily mediated by integrins [14,15]. The Haptides are relatively rich in both basic amino acids as well as cyclic hydrophobic groups, and are rapidly internalized into cells and can promote liposome uptake at nonsaturable kinetics, with no apparent cytotoxic effect [12,13].…”
Section: Introductionmentioning
confidence: 99%